Influence of Wheel Flat Scar Dynamic Impact on Vertical Vibration Characteristics of the Vehicles - Zhanghong LIU; Yang LI; Wenqiang FU; Yuchao WU; Yongge CAI (机车电传动)
In the process of high-speed operation of railway vehicles, the local tread scratches and stripping caused by emergency braking or wheel pair skidding and idling are collectively referred to as wheel flat scar. Based on computational multi-body dynamics and wheel-rail contact theory, a dynamic model of EMUs considering flat scar impact was established to simulate the dynamic response characteristics of vehicles. On the basis of this model, the influence of old and new flat scar and geometric dimensions wheel pairs on the dynamic behavior of vehicle system was studied. The vibration status of vehicle body, frame and axle box at different speeds was given, and the influence of wheel flat scar on dynamic performance under high-speed driving conditions was determined. The results showed that wheel flat scar has a great influence on wheel-rail contact and axle box vertical excitation of high-speed EMUs. Under the action of wheel flat scar, wheel rail impact and axle box vibration are much more serious than that of normal wheel rail; on the other hand, due to the existence of low-frequency filtering function of primary spring and secondary air spring, the influence of wheel flat scar vibration excitation on frame and body is weakened.